Development of p resonant current control for dc motor by using Arduino - Deraman, Farih (2014)
The DC motors have been popular in the industry control area for a long time because DC motors have many good features. Generally, DC motor speed is controlled by using potentiometers, variable resistors, and pulse-width-modulation. Speed control also can be achieved by variable battery tapping, variable supply voltage, resistors or electronic controls. But the problems in applying this conventional control method are the effects of nonlinearity in a DC motor. This project presents the development of Proportional Resonant (PR) current control for DC Motor. P Resonant (PR) type controller has been proposed to overcome the problem using MATLAB/Simulink software. This technique was called current control technique by comparing the actual current with the reference current at PR controller. Then, the Simulink model downloaded into Arduino to generate PWM signal. This signal was used to trigger the MOSFET at the rectifier circuit in order to control the current at DC motor. A set of hardware was designed and developed to demonstrate the validity of this approach. The observation and experimental results were explained in this report base on the PWM output and output current at DC motor.